Fitting and flailing: recognition of paediatric antiphospholipid syndrome. Issue 1 (3rd October 2013) - Freeman, H; Patel, J; Fernandez, D; Sharples, P; Ramanan, A V
Abstract : Antiphospholipid syndrome (APS) is a systemic autoimmune condition where the presence of antiphospholipid antibodies is thought to predispose to thrombotic events. It is uncommon in the paediatric population, but current diagnostic criteria are based on adult population studies, making assessment of its true paediatric prevalence difficult. We present two cases of paediatric APS, who presented with primary neurological events, and discuss approaches to diagnosis, interpretation of screening investigations, including antinuclear antibodies (ANA), anti-extractable nuclear antigen (ENA) antibodies and lupus anticoagulant. Possible approaches to the management of paediatric APS are discussed.